Design and Testing of Stream as a Sterilization Tool for Trichoderma sp. Propagation Media Using a Palm Oil Mill Steam Boiler - Fajri, Ihsanul; Hartulistiyoso, Edy; Widyastuti, Rahayu (The University of Lampung, 2025)
Trichoderma sp. is a fungus used in oil palm plantations to control basal stem rot disease, which can reduce palm oil production by up to 80%. At PT. Bumitama Gunajaya Agro, the production of this fungus uses an autoclave, which can only produce 51 kg of Trichoderma sp. per day per unit. To meet the high demand for Trichoderma sp., a large-capacity sterilization tool called